Efficacy and Safety of Sustained-Release Recombinant Human Growth Hormone in Korean Adults with Growth Hormone Deficiency - Kim, Youngsook (Yonsei University College of Medicine, 2014)
PURPOSE: The administration of recombinant human growth hormone in adults with growth hormone deficiency has been known to improve metabolic impairment and quality of life. Patients, however, have to tolerate daily injections of growth hormone. The efficacy, safety, and compliance of weekly administered sustained-release recombinant human growth hormone (SR-rhGH, Declage™) supplement in patients with growth hormone deficiency were evaluated. MATERIALS AND METHODS: This trial is 12-week prospective, single-arm, open-label trial. Men and women aged ≥20 years with diagnosed growth hormone deficiency (caused by pituitary tumor, trauma and other pituitary diseases) were eligible for this study. Each subject was given 2 mg (6 IU) of SR-rhGH once a week, subcutaneously for 12 weeks. Efficacy and safety at baseline and within 30 days after the 12th injection were assessed and compared. Score of Assessment of Growth Hormone Deficiency in Adults (AGHDA score) for quality of life and serum IGF-1 level. RESULTS: The IGF-1 level of 108.67±74.03 ng/mL was increased to 129.01±68.37 ng/mL (p=0.0111) and the AGHDA QoL score was decreased from 9.80±6.51 to 7.55±5.76 (p<0.0001) at week 12 compared with those at baseline. Adverse events included pain, swelling, erythema, and warmth sensation at the administration site, but many adverse events gradually disappeared during the investigation. CONCLUSION: Weekly administered SR-rhGH for 12 weeks effectively increased IGF-1 level and improved the quality of life in patients with GH deficiency without serious adverse events.